Identification of a Second Arcanobacterium pyogenes Neuraminidase and Involvement of Neuraminidase Activity in Host Cell Adhesion - Jost, B. Helen (American Society for Microbiology, 2002)
Arcanobacterium pyogenes, a common inhabitant of the upper respiratory and urogenital tracts of economically important animals, such as cattle and swine, is also an opportunistic pathogen associated with suppurative infections in these animals. A. pyogenes expresses neuraminidase activity encoded by the nanH gene, and previously, construction of a nanH mutant of A. pyogenes BBR1 indicated that a second neuraminidase is present in this strain. A 5,112-bp gene, nanP, was cloned and sequenced, and this gene conferred neuraminidase activity on an Escherichia coli host strain. The predicted 186.8-kDa NanP protein exhibited similarity to a number of bacterial neuraminidases and contained the RIP/RLP motif and five copies of the Asp box motif found in all bacterial neuraminidases. As expected, insertional inactivation of the nanP gene in A. pyogenes BBR1 resulted in a mutant with reduced neuraminidase activity. However, insertional inactivation of the nanP gene in the nanH mutant strain resulted in a complete lack of neuraminidase activity. Like NanH, NanP was localized to the A. pyogenes cell wall. However, unlike the nanH gene, which was present in 100% of the strains examined, nanP was present in only 64.2% of the isolates (n = 53). A. pyogenes adheres to HeLa cells, and a nanP mutant displayed a wild-type adhesion phenotype with these cells. In contrast, the ability of a nanH nanP double mutant to bind to HeLa cells was reduced by 53%. The wild-type adhesion phenotype was restored by providing nanP in trans. These data indicate that the neuraminidases of A. pyogenes play a role in adhesion of this organism to host epithelial cells.